2012
DOI: 10.1186/1471-2458-12-81
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and height over three generations: evidence from the Lifeways cross-generational cohort study

Abstract: BackgroundObesity and its measure of body mass index are strongly determined by parental body size. Debate continues as to whether both parents contribute equally to offspring body mass which is key to understanding the aetiology of the disease. The aim of this study was to use cohort data from three generations of one family to examine the relative maternal and paternal associations with offspring body mass index and how these associations compare with family height to demonstrate evidence of genetic or envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
96
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(107 citation statements)
references
References 27 publications
8
96
0
3
Order By: Relevance
“…The study is one of very few containing data on grandparents of both lineages, with at least one grandparent recruited at baseline. A summary of publications related to diet and cross-generation transmission to date for the Lifeways cohort study is given in Table 3 (107)(108)(109)(110)(111)(112)(113)(114)(115)(116)(117)(118)(119)(120)(121) . These analyses in this cohort have been consistent in showing an influence on health outcomes at different time points of lifestyle factors including diet and of cross-generation and familial associations.…”
Section: Prospective Studies With Information On Diet and Parental Bmimentioning
confidence: 99%
See 2 more Smart Citations
“…The study is one of very few containing data on grandparents of both lineages, with at least one grandparent recruited at baseline. A summary of publications related to diet and cross-generation transmission to date for the Lifeways cohort study is given in Table 3 (107)(108)(109)(110)(111)(112)(113)(114)(115)(116)(117)(118)(119)(120)(121) . These analyses in this cohort have been consistent in showing an influence on health outcomes at different time points of lifestyle factors including diet and of cross-generation and familial associations.…”
Section: Prospective Studies With Information On Diet and Parental Bmimentioning
confidence: 99%
“…A number of analyses have been undertaken across the generations of participating families related to the wave when children now averaged age 5 years (116)(117)(118) . Although the responses were received for just 669 of 1126 women originally recruited and not all of these had complete examination data, there was no significant difference in baseline maternal BMI in this sweep's participants compared with that of non-participants, although these mothers were older on average than nonparticipants.…”
Section: Follow-up When Children Averaged Age 5 Yearsmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Previous studies examining the strengths of associations of both maternal and paternal prepregnancy BMI with childhood outcomes have mainly focused on childhood BMI and have reported inconsistent results. 5,[8][9][10][11][23][24][25] Most studies reported no differences in the magnitude of parental associations with offspring BMI. [8][9][10][11]24 However, in childhood, BMI might not be an appropriate measure of fat mass.…”
Section: Interpretation Of Main Findingsmentioning
confidence: 99%
“…M ultiple intergenerational connections have been observed between maternal conditions and child health outcomes: from body mass index (Murrin et al, 2012) to age of menarche (Deardorff et al, 2012). Consequently, poor health may be transmitted from parents to children, conceivably perpetuating health disparities and providing reason to consider intergenerational determinants in disease prevention.…”
mentioning
confidence: 99%